The new Muslim Brotherhood in the West - Vidino, Lorenzo (Columbia studies in terrorism and irregular warfare., 2010)
In both Europe and North America, organizations tracing their origins back to the Muslim Brotherhood and other Islamist movements have rapidly evolved into multifunctional, richly funded organizations. They now compete to become the major representatives of Western Muslim communities and government interlocutors. Some analysts and policy makers see these organizations as positive forces encouraging integration. Others treat them as modern-day Trojan horses that feign moderation while radicalizing Western Muslims. Lorenzo Vidino brokers a third and more informed view. Having compl.